Assessment of Iodine Deficiency in Pregnant Women and Neonates in the Capital Territory of Pakistan - Zafeer, N.; Altaf, J.; Rafi, M.; Chaudhry, M. M.; Qayyum, M.; Naz, S. (The Nucleus, 2019)
One of the major nutritional problems in Pakistan is the deficiency of iodine in different groups of population, e.g., pregnant women and neonates. The neonates and their expectant mothers have been significant target groups of the population to be studied for the deficiency of iodine. The objective of the present research work was to evaluate the status of iodine deficiency in neonates and their mothers in Islamabad, Pakistan. A hospital based study was carried out on two hundred sixty one pregnant women and one hundred twenty five neonates of these women, to find out iodine level among these samples. Fifty healthy and non pregnant women were used as control in the maternity and gynecological unit of the hospitals of Islamabad. The status of iodine of the pregnant and non-pregnant women was assessed by catalytic reduction method. Thyroid function was assessed by determining the concentration of TSH in the cord blood of neonates using radioimmunoassay technique, in the environmental laboratory of the Chemical and Materials Engineering Department at Pakistan Institute of Engineering and Applied Sciences (PIEAS) Islamabad. Ninety-four percent pregnant women and ninety-eight percent non-pregnant women exhibited urinary iodine concentration (UIC) between 20 µg/L to 99 µg/L respectively. It indicates that there was severe to mild iodine deficiency in population of study area. The median values of urinary iodine concentrations in the pregnant women and control group were 30.37 µg/L and 19.08 µg/L respectively. Statistically it was found that there was a significant (p<0.05) difference between the levels of urinary iodine concentration of non-pregnant and pregnant women. It was also found that there was a non-significant (p>0.05) difference in the concentration of urinary iodide between the pregnant women of different age groups. An overall 57.14% neonates exhibited TSH levels >5 mIU/L. From these results, it is concluded that the pregnant women had moderate iodine deficiency while their neonates had severe iodine deficiency. Keeping in view these results it is suggested that the practice of iodized salt utilization could be continued, and it is recommended that the screening of neonates or TSH levels should be compulsory in the iodine deficient areas.